In vivo pH and metabolite changes during a single contraction in rat uterine smooth muscle - Larcombe-McDouall, Jacky (Blackwell Science Inc, 1999)
1. We have used (31)P NMR spectroscopy to measure metabolites and pH(i) at three periods during a phasic contraction of the uterus, in vivo, to determine whether they change as a consequence of contraction. The regular uterine contractions were recorded via a balloon catheter in the uterine lumen. Each phasic contraction was divided into three parts: the period between contractions (rest), the development of force (up) and the relaxation of force (down). The NMR data were summed separately from each of these three periods over 20-40 successive contractions. 2. Significant changes in ATP, phosphocreatine (PCr) and inorganic phosphate (P(i)) occurred during the contraction. [ATP] fell from 2.0 to 1.6 mM and [PCr] from 2.6 to 2.0 mM during the up period, while [P(i)] increased from 2.2 to 2.8 mM. Recovery of ATP and PCr occurred during the relaxation part of the contraction, whereas P(i) did not fully recover until the contraction was complete. 3. Significant acidification from pH 7.28 ± 0.02 at rest to 7.16 ± 0.02, occurred with contraction. This acidification is greater than that previously reported for in vitro uterine preparations. Measurements of uterine blood flow show that it decreased with contraction. Therefore, ischaemia, in addition to the metabolic consequences of contraction, may account for the larger acidification observed in vivo. 4. Lowering pH(i) in an in vitro uterine preparation by a similar level to that found in vivo produced a significant reduction of the phasic contractions. Thus we propose that these changes, especially the fall in pH(i) during force development, feed back negatively on the contraction to limit its strength, and may help prevent uterine ischaemia and fetal hypoxia during labour.